Simultaneous cardiac and cerebral infarction ‒ a case report - Kyaw, May Thu (Rzeszów University Press, 2026)
Introduction and aim. Concurrent cardiocerebral infarction (CCI) is a rare condition defined by the simultaneous presentation of acute myocardial infarction (AMI) and acute ischemic stroke (AIS). This case report aims to illustrate the clinical presentation, diagnostic challenges, and treatment considerations in a patient with CCI. Description of the case. We describe the case of a 61-year-old Asian patient with symptoms of AMI, which was successfully treated with primary percutaneous coronary intervention (PCI). Six hours after the initial presentation, the patient developed symptoms of AIS. Imaging revealed an acute infarct in the left globus pallidus and small lacunar infarcts in the left thalamus region. Due to the location of the cerebral infarct, the patient was managed conservatively for AIS. The patient showed a positive response to the treatment, with no recurrence of chest pain or neurological symptoms observed at the six-month follow- up. Conclusion. This case emphasizes the importance of prompt brain imaging to distinguish between different types of stroke and highlights the challenges in managing CCI, a condition linked to high mortality and morbidity. Early recognition and tailored therapy are crucial for improving prognosis.
Keywords: acute ischemic stroke; acute myocardial infarction; cardio-cerebral infarction; percutaneous coronary intervention